Performance study of a new parabolic trough design under optical concentrator effect. (25th January 2023) - Habchi, A.; Hartiti, B.; Labrim, H.; Fadili, S.; Faddouli, A.; El hajjam, N.; Thevenin, P.; Ntsoenzok, E.
Highlights: A new hybrid parabolic trough concentrator is proposed. A new algorithm for the hybrid trough concentrator is presented. The influence of the optical concentrator on the hybrid system performance is studied. Results showed a maximum thermal efficiency of 86 % corresponding to 318.9 Watts as additional electrical power while the heat losses are reduced from 2.76% to 1.9%. The chemical interactions within Therminol VP1 stay stable and the hydrogen production rate remains at 2.90 µmol/kg/h, reducing the possibility of cracking problems. Abstract: The production of thermal and electrical energy by conventional and hybrid parabolic trough concentrators is widely considered most important in the field of renewable systems. In this work, two main problems of parabolic trough concentrators were studied with the aim of minimizing them as much as possible, namely, the cracking of Therminol VP1 and heat loss. The cracking problem of Therminol VP1 is one of the major troubles of parabolic trough systems at high temperatures (400 °C) due to its dramatic consequences, which decrease significantly the thermal and electrical efficiency of parabolic trough concentrator. To address these issues, the temperature of Therminol VP1 was automatically controlled by a new parabolic trough concentrator integrated with two different types of tubular thermoelectric generators. A new mathematical model was offered for this hybrid system. In addition, a set of thirteen non-linear equations were discretized using the finite difference method. The discretized equations were coded in MATLAB (2015a) software based on the Gauss-Seidel technique with an accuracy of 0.001. To confirm the predicted results of the new numerical model, a literature paper was used for comparison. The comparison between the predicted and literature results was in good agreement. The effect of solar concentrator ratio on the thermal and electrical performance of the new system was analyzed and discussed. The major results show that the maximum thermal efficiency of the new system up to 86 % corresponding to 318.9 Watts of additional electrical power. Also, the maximum storage of hot water at 95 °C and Therminol VP1 at 400 °C up to 251.5 Liter/Day and 383.8 Liter/Day, respectively. Additionally, the cracking problem of Therminol VP1 was effectively controlled. More precisely, the hydrogen generation rate was automatically stabilized at a low and stable value of 2.90 µmol/kg/h. In addition, the heat losses rate was reduced from 2.97% to 1.07% with increasing solar concentration ratio. These results represent a useful reference for the selection of this new hybrid parabolic trough concentrator in view of its developed and intelligent performance.